PENDIDIKAN KARAKTER DI PESANTREN - Fahham, Achmad Muchaddam (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2013)
This article is written in order to understand the characteristic of Islamic boarding school as well as to explain some values required in forming the character of students and implementation strategies of character education in Islamic boarding school. The results of this study concluded that the boarding school is an educational institution that implemented integral character education in the overall process of education and learning. Hence, it formed the typical boarding school culture that distinguishes it from other education system of non-Islamic boarding school. Values being developed in Islamic boarding school help its students in building their characters through five principles of sincerity, simplicity, independency, brotherhood guided by the spirit of religion, and freedom. In addition to that, in general, modern Islamic boarding schools have followed the path of Gontor Modern Islamic Boarding School who developed a motto of healthy, knowledgeable, and free-thinking. Those values are then being fully implemented in not only learning process, but also in the formation of Islamic boarding school culture, co-curricular activities, and extra-curricular activities.